The emergence and proliferation of agroholdings and mega farms in a global context - Frans Hermans; Fabio Chaddad; Taras Gagalyuk; Sebastián Senesi; Alfons Balmann (International Food and Agribusiness Management Review, 2017)
During the last two decades an increasing amount of large-scale farming operations have emerged all over the world: from (Eastern) Europe, to South America, China and the countries of the Former Soviet Union. These agribusinesses go under the name of mega-farms or agroholdings: horizontally or vertically integrated operations with farm sizes of up to 500,000 hectares and sometimes even more. These types of farms are not only found in crop farming, but also in animal husbandry. Although some information on agroholdings and other forms of mega-farming operations is available, a systematic analysis of their prevalence, economic performance as well as their social and environmental implications in an international perspective is missing. In this special issue of the International Food and Agribusiness Management Review we present a number of papers that highlight the different aspects of such farms. In this editorial we introduce the topic of agroholdings and place the papers in within the context of the available literature. We end with the presentation of a research agenda for the future.
Keywords: Q13; Q14; Q16; 330; agroholdings; mega farms; integration; farm size